The effect of one-way aisles on retail layout. (June 2022) - Urban, Timothy L.
Highlights: Due to the COVID–19 pandemic, many retailers have implemented one-way aisles. The increase of in-store customer traffic flow for one-way vs. two-way aisles is evaluated. Due to backtracking, the proportion of the store layout that the shopper visits is also considered. Both measures are shown to be substantial and statistically significant. Additional insights concerning the continued use of one-way aisles are presented. Abstract: As part of the initiative to prevent the spread of the novel coronavirus (COVID–19), many retailers implemented one-way aisles in their stores. Moreover, the retailing research literature has shown a significant positive relationship between the distance that shoppers travel within the store and their resulting unplanned purchases. To evaluate the effect that one-way aisles have on the amount of traffic flow in the store, we use the traveling salesperson problem to determine the increase in distance traveled as well as the increase in the area within the store that is covered by the shopper. Overall, our results indicate that shoppers may travel 50 percent further with one-way traffic and cover an additional 67 percent of the store area, a significant increase in the amount of product and in-store stimuli exposed to the customer. We also present other advantages and disadvantages of the continued use of one-way aisles after the pandemic subsides.